Penilaian Efektivitas Penerapan Teknis Restorasi Gambut Melalui Program Desa Mandiri Peduli Gambut di Desa Pasir Palembang - Mishbaahul Fajar; Hastanto Bowo Woesono; Didik Surya Hadi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The importance of peat ecosystems in carbon absorption and providing habitat for various types of flora and fauna. However, peatland damage due to land conversion and forest fires has become an urgent problem to be addressed. The Independent Village Care for Peat Program is a government initiative that aims to involve communities in peat restoration efforts, so it is important to assess the effectiveness of this program at the village level. The methodology used in this study is a descriptive method with a qualitative and quantitative approach. Data collection was carried out through field observations, in-depth interviews with communities and stakeholders, and analysis of related documents. The research sample involved the Pasir Palembang Village community involved in the peat restoration program, peat restoration technical personnel in the field, and government parties related to the program. The results of the study showed that the technical implementation of peat restoration in Pasir Palembang Village through the Independent Village Care for Peat Program was quite effective in several aspects, such as controlling forest and land fires. However, there are several challenges that need to be overcome, such as the lack of adequate resources and funding. Active community participation and government support have proven to be key factors in the success of this program. Factors influencing the success of the peat restoration program in Pasir Palembang Village include community support and involvement, resource availability, government policies, and natural and climate conditions in the village. Socialization and education to the community regarding the importance of peat restoration need to be improved, and resource and funding support needs to be optimized for the sustainability of the program. Cross-sectoral collaboration between the government, community, and non-governmental organizations is also important to strengthen peat restoration efforts. The conclusion of this study is that the technical implementation of peat restoration through the Independent Peat Care Village Program in Pasir Palembang Village is quite effective, but still needs improvement in several aspects to achieve more optimal results. Recommendations given include increasing socialization and education, optimizing resource and funding support, and developing cross-sectoral collaboration to strengthen peat restoration efforts.